Evaluation of Alpha Particle Emission Rate Due to the p-11B Fusion Reaction in the Large Helical Device. (3rd April 2022) - Ogawa, K.; Isobe, M.; Nuga, H.; Seki, R.; Ohdachi, S.; Osakabe, M.
Abstract: A numerical study of the alpha particle emission rate due to the p- 11 B fusion reaction based on the respectively obtained Large Helical Device (LHD) plasma parameters in an experiment is performed. First, the total alpha particle emission rate is estimated by employing the beam ion distribution calculation code FIT3D and the fusion reaction rate calculation code FBURN based on the classic confinement of beam ions. Then, the calculation is performed using hydrogen-beam-heated hydrogen plasma parameters and the radial boron density profile obtained from boron drop discharge. The result shows that the total alpha particle emission rate reaches approximately 10 14 s −1 . Then, based on the radial profile of the alpha particle emission calculated by the FBURN code, the distribution of the first orbit loss of5.78-MeV alpha particles created by the p- 11 B reaction on the vacuum vessel and the divertor plate is calculated by the collisionless Lorentz orbit code LORBIT. Although most of the alpha particles are lost to the divertor plate, some of the alpha particles are lost on the vacuum vessel. Finally, a feasibility study of alpha particle detection by the existing manipulators and fast ion loss detector position is performed. The number of particles as a function of position shows that a substantial number of alpha particles can be detected. Alpha particles with a pitch angle of ~130 deg can reach manipulator positions. In contrast, particles with pitch angles of ~50 and ~110 deg can reach the fast ion loss detector position. The calculation shows that measurement of alpha particles due to p- 11 B is thought to be possible using charged particle detectors.